If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2xy + 3xy + -1x + 3xy = 0 Reorder the terms: -1x + -2xy + 3xy + 3xy = 0 Combine like terms: -2xy + 3xy = 1xy -1x + 1xy + 3xy = 0 Combine like terms: 1xy + 3xy = 4xy -1x + 4xy = 0 Solving -1x + 4xy = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Factor out the Greatest Common Factor (GCF), 'x'. x(-1 + 4y) = 0Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(-1 + 4y)' equal to zero and attempt to solve: Simplifying -1 + 4y = 0 Solving -1 + 4y = 0 Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 4y = 0 + 1 Combine like terms: -1 + 1 = 0 0 + 4y = 0 + 1 4y = 0 + 1 Combine like terms: 0 + 1 = 1 4y = 1 Add '-4y' to each side of the equation. 4y + -4y = 1 + -4y Combine like terms: 4y + -4y = 0 0 = 1 + -4y Simplifying 0 = 1 + -4y The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
x = {0}
| (10x+6/2)-(4x-8/9)=(8x-8/3) | | 4x+3y-x+3xy= | | 2x+5x=1 | | 5(y-2)=25 | | x+x+x=x+6 | | m+24=33 | | 3xy+2x-3y+7= | | 7-2n=3n-38 | | 10x+6/2-4x-8/9=8x-8/3 | | 2(7x-1)=96 | | 4x-x+3y-y= | | -7(6v+5)=91 | | -6a+5(1-2a)=101 | | -10x+3y-4xy+5= | | 2k^3-36k^2=162k | | -3x+5y+3+3x-5y= | | -45=3n+9 | | (x-(2+3i))(x-(2-3i))=0 | | -5+7x-2+3x+y-8y+6= | | 10r+8=-182 | | -3xy+3xy= | | 2x+2=-2x+6 | | 2x+2=x-1 | | 5z/8=85 | | -9=x-2 | | -6(1-3x)-5x=85 | | 25x+y=13x-y | | -2+5(4n+7)=173 | | -11y^2-27=0 | | r-36=14.7 | | 250Q-2-2.5+1Q=0 | | h^2+81=0 |